PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL NESTEDBERBASIS INKUIRI TERBIMBING UNTUK MENINGKATKAN PEMAHAMAN KONSEP, THINKING SKILL, DAN SOCIAL SKILL PADA SISWA SMP - Choiriyah, Fitrotul; Madlazim, Madlazim; Haryono, Tjipto (Universitas Negeri Surabaya, 2017)
This research was done by developing learning materials (lesson plans, student’s worksheets, textbooks students, test understanding of the concept, Thinking skill and Social Skill) nested models based guided inquiry by using 4D development model to improve the understanding of the concept, thinking skills and social skills on the subject of light. The objective of this research is trial learning materials for 32 of junior high school’s students with the design of the one-group pretest-posttest design. Result was analyzed by descriptive quantitative - qualitative with: (a) validity of learning material is very valid category; (b) learning realization with good category; (c) the students response are positive; (d) student’s understanding of the concept is increased (high criteria); (e) thinking skill is increased (high criteria); (f) social skill increased in every meeting. In conclusions of this research, the nested model based learning guided inquiry concepts can improve the understanding concept, thinking skills, and social skill of junior high school